Порівняльний аналіз показників захворюваності школярів із різними вадами слуху - Маслова, Олена Володимирівна; Гопей, Максим Миколайович; Maslova, Elena; Gopey, Maksim (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статі представлено результати аналізу даних дослідження показників захворюваності школярів із приглухуватістю та глухотою з урахуванням їхнього віку й статі. Вивчення захворюваності школярів із різними вадами слуху проводили на основі викопіювання їхніх даних із медичних карток і систематизування за трьома показниками: вид захворюваності, структура захворюваності та тимчасова втрата працездатності. Отримані дані підтверджують негативну ситуацію погіршення стану здоров’я школярів України, що поглиблюється серед учнів зі встановленими вадами слуху. Спостерігають кількісне зростання функціональних розладів, гострої та хронічної соматичної захворюваності, синдрому дезадаптації, вроджених вад розвитку, морфофункціональних відхилень. Викликає чималу стурбованість і той факт, що збільшується кількість дітей з установленими вадами слуху й із розладами психіки та поведінки. The article presents the results of data analysis studies of schoolchildren morbidity indicators with hearing impairment and deafness in accordance with their age and gender. The study of the incidence of schoolchildren morbidity with a variety of hearing impairment was carried out on the basis of their data to the copy of the medical records and systematization for three indicators: the type of disease, morbidity structure and temporary disability. The aim of study was a comparative analysis of schoolchildren morbidity with different hearing disorders. Objectives of the study: to determine the schoolchildren indicates morbidity with different hearing impairments; to establish subjective risk factors deterioration for children with hearing loss. Research methods: analysis and synthesis of specific scientific and methodological literature data; monitoring of information resources on the Internet; the copy method, with the prior consent of the parents, personal data from children medical cards; systematic approach; methods of mathematical statistics. These data confirm the negative situation the deterioration of the schoolchildren health in Ukraine is aggravated by among pupils with established hearing impairments. There is a quantitative growth of functional disorders, acute and chronic somatic diseases, syndrome disadaptation, congenital malformations, morphological and functional abnormalities. It is of great concern and the fact that an increasing number of children with hearing impairments and installed with mental disorders and behavior.
Сomparative Analysis of Schoolchildren Morbidity with Different Hearing Disorders
Keywords: захворюваність; хвороба; школярі; слабочуючі; приглухуватість; глухота; morbidity; illness; schoolchildren; hearing impaired; hearing loss; deafness